The Effect of Motivation and Leadership on Employee Job Satisfaction in Improving Employee Performance PT. Artha Valasindo Mandiri (AVM) - Desy Natalia Gushendra; Subagja, Iwan Kurniawan; Hary Indratjahyo (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to: 1) determine and analyze the effect of motivation on job satisfaction, 2) determine and analyze the effect of leadership on job satisfaction, 3) determine and analyze the effect of motivation on employee performance, 4) determine and analyze the effect of leadership on employee performance, 5) determine and analyze the effect of job satisfaction on employee performance, 6) determine and analyze the effect of motivation on employee performance through job satisfaction, and 7) determine and analyze the effect of job satisfaction on employee performance through job satisfaction. The study was conducted at PT. Artha Valasindo Mandiri (AVM), with a research sample of 50 respondents. The sampling technique used was saturated. The data analysis method uses descriptive analysis and path analysis. The results of the study indicate that: 1) there is an influence of motivation on job satisfaction, 2) there is an influence of leadership on job satisfaction, 3) there is an influence of motivation on employee performance, 4) there is an influence of leadership on employee performance, 5) there is an influence of job satisfaction on employee performance, 6) there is an influence of motivation on employee performance through job satisfaction, and 7) there is no influence of job satisfaction on employee performance through job satisfaction.